Design Research to Learn Mathematics: A Study on The Effect of Problem-Solving Ability on The Creative Attitude of Junior High School Students - Nilam Sari; Sahat Saragih; E. Elvis Napitupulu (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
This study examines the background of problem-solving ability and creative attitudes among junior high school students, highlighting their importance in fostering innovation and critical thinking in mathematics education. The purpose of this study is to analyze the influence of problem-solving ability on students' creative attitudes. The classroom process is a learning process that develops local instructional theories for the material of systems of linear equations in two variables. The quantitative study aims to assess the influence of problem-solving ability on students' creative attitudes. This study involved 24 junior high school students in Medan as a sample. The instruments used were a validated problem-solving ability test and a validated creative attitude scale. The results showed that problem-solving ability has a significant positive effect on students' creative attitudes, with a regression coefficient of 0.951, indicating that greater problem-solving ability is associated with stronger creative attitudes. The coefficient of determination (R² = 0.597) indicates that 59.7% of the variation in students' creative attitudes is due to problem-solving ability. In contrast, friendship (40.3%) is due to other factors not examined in this study. These findings suggest that problem-solving ability is a key factor in developing creative attitudes. This study highlights the need to integrate problem-solving ability into the educational curriculum to foster students' creative attitudes. Future research should consider using a larger sample size.